Brooding in the southern ocean: The case of the pterasterid sea star diplopteraster verrucosus (sladen, 1882) - Fraysse, Cintia Pamela; Boy, Claudia Clementina; Becker, Yamila Anabella; Calcagno, Javier Ángel; Pérez, Soledad Analía (The Biological Bulletin)
Diplopteraster verrucosus is a sea star that incubates its offspring in nidamental chambers. The offspring rely exclusively on maternally provided nutrition. The retention of the embryonic stages allows the allocation of nutritional supplies fromthe female to the brooded juveniles during the brooding period. Themain objectives of this study are, first, to quantify the reproductive investment of D. verrucosus and, second, to describe the morphology, energetics, and oxidative metabolism throughout early ontogenetic stages. A skewed sex ratio of 2:1 females:males was found, and 17 of 39 females were brooding. Both brooding and non-brooding females showed higher energy density and total antioxidant capacity in their gonads than males. We identified three cohorts of offspring being retained within the female body simultaneously. Energy density and reactive oxygen species increased significantly with the offspring’s volume throughout ontogeny. Moreover, we found evidence of at least two key events during ontogeny. First, the depletion of antioxidants, the increase of reactive oxygen species, and the development of a complete digestive system appear to trigger feeding on the mothers’s pyloric caeca. Second, another oxidative imbalance appears to be associated with the release of the brooded juveniles to the environment. Therefore, oxidative balance and energetic variances may be associated with development of autonomous feeding and juvenile release in D. verrucosus. Fil: Fraysse, Cintia Pamela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Maimonides. Centro de Ciencias Naturales, Ambientales y Antropologicas.; Argentina Fil: Boy, Claudia Clementina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Becker, Yamila Anabella. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Calcagno, ...